2011
DOI: 10.5392/ijoc.2011.7.2.017
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Technophobia and Mobile Device Design

Abstract: Technophobia is described as the 'abnormal fear or anxiety about the effects of advanced technology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
1
12
0
1
Order By: Relevance
“…This anxiety towards learning could suggest why a high proportion of the respondents did not attend any form of computer training. This observation buttresses Ha et. al's (2011) assertion to the effect that further development of internet technologies and sophisticated mobile phones will inevitably lead to more people becoming technophobic.…”
Section: Factors Influencing Cbit Technophobiasupporting
confidence: 84%
See 2 more Smart Citations
“…This anxiety towards learning could suggest why a high proportion of the respondents did not attend any form of computer training. This observation buttresses Ha et. al's (2011) assertion to the effect that further development of internet technologies and sophisticated mobile phones will inevitably lead to more people becoming technophobic.…”
Section: Factors Influencing Cbit Technophobiasupporting
confidence: 84%
“…This implies that lack of training contributed to this level of agreement; as more than half (62.8 percent) of the respondents did not experience any formal computer training (Table 1) and this could suggest that respondents do not use CBIT in the dissemination of information. Secondly, the expressed level of CBIT technophobia and unfamiliarity with CBIT could be as a result of poor internet facilities and power supply in the rural area where they operate; and, • I feel I will not be able to keep up with the advances in computer field (incidence index .25; rank 15) This indicates that respondents' level of CBIT technophobia is based on the perception that CBITs are complex (Ha et al, 2011). This observation is further supported by Rheingold (2002) who indicated that when people perceive a technology to be complex and advanced, it is more likely they would become technophobic and may avoid the use of such technology despite its perceived benefits.…”
Section: Distribution Of Respondents Based On the Incidence Of Cbit Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Technophobia (or computerphobia) is defined as irrational fear or anxiety about the impact of advanced technology (Ha, Page, & Thorsteinsson, 2011). Technophobia is evidenced by the presence of one or more of the following: anxiety about current or future interactions with computer-related technologies; overall negative attitudes toward computer-related technologies, their behaviors, and/ or social impacts; and specific negative cognitions of self-critical internal dialogues in actual computer-related technology interactions or when considering future interactions (Rosen & Weil, 1990).…”
Section: Technophobia and Anxietymentioning
confidence: 99%
“…Sin embargo, es conocido que, a pesar de sus ventajas, cualquier innovación técnica, como las anteriormente mencionadas, se enfrenta en los primeros estadios de su implantación a resistencias por parte de los diferentes grupos que participan en la actividad: desde los directivos a los consumidores o usuarios, pasando por el personal que interviene en la fabricación del producto o la prestación del servicio. Durante la primera década del siglo XXI, autores como Ha et al (2011) y Sinkovics et al (2002) estudiaron la tecnofobia, su medición y distintas formas de evitarla (Chukhray, 2012).…”
Section: Introductionunclassified